Effect of Al doping on band gap of pentagonal cross section SiNWs. (1st January 2014) - Kausar, Sana; Joshi, Shirish; Srivastava, Anurag
In this work band structure of silicon nanowires (SiNWs), oriented along [111] direction having pentagonal cross section was studied by using generalised geometry approximation (GGA). SiNWs was passivated with hydrogen. Further the effect of doping of aluminium atom on band structure of hydrogen passivated SiNWS is analysed. It is found that the band gap of Si nanowire get reduce on doping it with Al atom and doped nanowire starts behaving as bulk silicon.